U–Pb geochronology of Late Silurian (Wenlock to Pridoli) volcanic and sedimentary rocks, central Newfoundland Appalachians: Targeting the timing of transient extension as a prelude to Devonian orogenic gold mineralization - Honsberger, Ian W.; Bleeker, Wouter; Kamo, Sandra L.; Sutcliffe, Chelsea N.; Sandeman, Hamish A.I. (Atlantic Geoscience)

(untitled) (Atlantic Geoscience Society, 2022)
Bimodal igneous suites and associated immature clastic sedimentary rocks are characteristic of many orogenic gold-mineralized, crustal-scale fault zones globally. In the central Newfoundland Appalachian orogen, the Rogerson Lake Conglomerate belt and Botwood basin are Late Silurian (Wenlock to Pridoli), fault-controlled sedimentary rock sequences and magmatic suites closely associated with orogenic gold mineralization; however, the spatio-temporal evolution of faulting and associated sedimentation and magmatism are not fully resolved. U–Pb zircon geochronological results were obtained by using an integrated approach employing LA-ICPMS (laser ablation-inductively coupled plasma mass spectrometry) followed by CA-ID-TIMS (chemical abrasion-isotope dilution-thermal ionization mass spectrometry) on the same detrital samples. Using this approach, a maximum depositional age for sedimentary rocks of the Rogerson Lake Conglomerate sequence is 421.9 ± 1.0 Ma (Pridoli), which confirms that they are younger than, and stratigraphically overlie, ca. 422–420 Ma igneous rocks exposed along the central Newfoundland gold belt. Towards the stratigraphic middle of the Botwood basin in north-central Newfoundland, a tuffite layer intercalated with graded siltstone produced a maximum depositional age of 427.9 ± 3.1 Ma (Wenlock; Homerian). The age of emplacement of an autobrecciated, flow-banded rhyolite dome of the Charles Lake volcanic belt along the northwestern Botwood basin is 429.3 ± 0.7 Ma (Wenlock; Homerian). The high-precision CA-ID-TIMS zircon data establish a clear link between Wenlock to Pridoli magmatism and sedimentation throughout central Newfoundland. Furthermore, these geochronological results are consistent with a structural model involving the southeastward (present-day coordinates) advancement of a transient extensional fault system across strike of the Exploits Subzone between ca. 429 and 418 Ma, with propagation along strike to the southwest (Rogerson Lake Conglomerate belt) between ca. 422 and 418 Ma. Extensional faulting may have contributed to basin formation, subsidence, and exhumation of pre-Late Silurian rocks of the Exploits Subzone. Time-transgressive, extension-related magmatism and clastic sedimentation appear to mark the transition between the Salinic and Acadian orogenic cycles along the central Newfoundland gold belt. Transient Wenlock to Pridoli lithospheric extension may have been important for increasing heat and fluid flow in the crust as a prelude to Devonian crustal thickening, fluid focussing, and orogenic gold mineralization.